Incubation and hatching behaviour in the Mallard - McKinney, D F (Wildfowl, 1952)
An incubating duck remains on the nest continuously except for one or two periods each day when she leaves to feed and oil her plumage. These periods of absence usually occur in the morning or the evening, and they last from thirty to sixty minutes.